A community participatory approach to enhancing capacity in patient-centered alcohol research: Bridging translational science and empowering women - Pravesh Sharma; Hannah Kolarik; Christopher Plapparampil Benny; Brianna N. Tranby; Tessa Vance; Tommi Thompson; Kasey R. Boehmer; Alanna M. Chamberlain; Christi A. Patten (Journal of Clinical and Translational Science)
Alcohol misuse among women has risen compared to men. Women experience barriers to engaging in patient-centered comparative effectiveness research (CER) that, in turn, limits the evidence base for addressing alcohol misuse in this population. In this manuscript, we describe WomenWise, a community-partnered project and outline how we co-developed community focused CER training curriculum and collaboratively planned future partnered learning sessions (PLSs) with Community Advisory Board (CAB) feedback. Through this approach we aim to empower women to contribute to future patient-centered CER and enhance the stakeholder capacity for future patient-centered research.